Potentiated Hsp104 variants suppress toxicity of diverse neurodegenerative disease-linked proteins - Meredith E. Jackrel; James Shorter (The Company of Biologists, 2014)
Protein misfolding is implicated in numerous lethal neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and Parkinson disease (PD). There are no therapies that reverse these protein-misfolding events. We aim to apply Hsp104, a hexameric AAA+ protein from yeast, to target misfolded conformers for reactivation. Hsp104 solubilizes disordered aggregates and amyloid, but has limited activity against human neurodegenerative disease proteins. Thus, we have previously engineered potentiated Hsp104 variants that suppress aggregation, proteotoxicity and restore proper protein localization of ALS and PD proteins in Saccharomyces cerevisiae, and mitigate neurodegeneration in an animal PD model. Here, we establish that potentiated Hsp104 variants possess broad substrate specificity and, in yeast, suppress toxicity and aggregation induced by wild-type TDP-43, FUS and α-synuclein, as well as missense mutant versions of these proteins that cause neurodegenerative disease. Potentiated Hsp104 variants also rescue toxicity and aggregation of TAF15 but not EWSR1, two RNA-binding proteins with a prion-like domain that are connected with the development of ALS and frontotemporal dementia. Thus, potentiated Hsp104 variants are not entirely non-specific. Indeed, they do not unfold just any natively folded protein. Rather, potentiated Hsp104 variants are finely tuned to unfold proteins bearing short unstructured tracts that are not recognized by wild-type Hsp104. Our studies establish the broad utility of potentiated Hsp104 variants.